IMPROVING STUDENTS’ VOCABULARY THROUGH MAKE A MATCH TECHNIQUE - Utami, Nia; Sutapa, Gatot; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to find out how the use of Make a Match Technique improved vocabulary of tenth-grade students of Islamic Boarding School of Mathla’ul Anwar Pontianak in academic year 2018/2019. This research used Classroom Action Research with two cycles. The subjects of this research were 36 students of X IPS 2. The result showed that the use of Make a Match Technique improved the students’ vocabulary. In the teaching learning process, the students were more enthusiastic and paid more attention to the learning activity. Furthermore, from the administered assessment, it showed that the students expand their vocabularies and can understand the meaning when doing written test in the class. As the result, from the students’ individual score, it improved in each cycle. Therefore, the researcher recommends teachers to use Make a Match as a vocabulary teaching technique as to help students improve their vocabulary. Keywords: Vocabulary, Make a Match Technique